Analisis Durasi Berlari Berdasarkan Umur Dan Berat Badan Manusia Menggunakan Regresi Linear Berganda - Muhammad Thonthowi (Jejaring Penelitian dan Pengabdian Masyarakat (JPPM), 2026)
Running is an effective sport for improving fitness and burning calories. Running duration can be influenced by several factors, including age and body weight. These factors play a role in determining a person's endurance while running. Physiologically, individuals with a higher body weight tend to experience fatigue more quickly, while younger individuals generally have better endurance than those who are older. This study aims to analyze the relationship between age and body weight on running duration using the multiple linear regression method. The data used includes information on the individual's running duration, age and body weight, which is expected to provide deeper insight into the factors that influence running ability. The results of this research can be a basis for preparing exercise programs that are more appropriate to each individual's physical condition.